SECURITY SISTEM KELISTRIKAN MOTOR INDUSTRI MENGGUNAKAN MEDIA BLUETOOTH BERBASIS MIKROKONTROLER ATMEGA 328 - Al Husain; Fery Sudarto; Chandra Jayusman (UNIVERSITAS RAHARJA, 2016)
Developments in science and technology have been able to encourage people to address and resolve the problems that exist in everyday life. One of the technologies developed at this time is a microcontroller. Microcontroller is a chip that can perform digital data processing in accordance with a command programming language that so givent currently Microcontroller widely applied in daily life and industry, one for